Control system for aquatic biological resources in the Northern fisheries basin of Russia - S. S. Vopilovskii (Вестник университета)
The study of the Russian fishery management system aims to determine the degree of readiness of the fishing industry to implement economic processes of access to aquatic biological resources in the country’s Northern fishery basin. A comparative analysis of fishery management systems in a market economy (fishery complex of Russia) and a planned economy of the USSR has been presented. It has been determined that the allocation of aquatic biological resources for industrial fishing is managed on the basis of Russian regulatory legal acts, and the implementation of the tasks of developing the fishery sector and ensuring the country’s food security is consistent with the implementation of the Basic State Policy of Russia. Key performance indicators of the fishing industry, the system of allocation of fishing (catch) quotas for aquatic biological resources based on the “historical principle” and the “auction system” have been presented. The aim of the study is to assess the being implemented plans for the total allowable catch development, and the desire of the fishery management system and business to increase the economic potential of the Russian fishery sector.